LESSONS FROM “POLITICAL ENTREPRENEURSHIP”: PROJECT-BASED POLITICAL SCIENCE CLASSES APPLYING DESIGN THINKING - Sobari, Wawan (Erudio Journal of Educational Innovation, 2025)
Design-based learning (design thinking) and project-based learning (PBL) are innovative approaches that are increasingly relevant in Political Science education to improve students' critical, creative, and collaborative thinking skills. This study evaluates the application of design thinking in a Political Entrepreneurship Course over the past two years at Universitas Brawijaya, involving 145 students as participants. This study used a quantitative descriptive approach to measure changes in students' creative mindsets based on seven elements of design thinking: tolerance of ambiguity, empathy, and problem reframing. The results showed that most students felt comfortable working in complex situations, were able to build empathy for public needs, and produced innovative solutions through design iterations. This approach has proven effective in encouraging active student engagement and creating prototypes that are relevant to real contexts. This study makes a significant contribution to enriching political science pedagogy through the integration of design thinking and PBL and underlines the importance of this approach in training future generations of leaders. The findings recommend strengthening cross-disciplinary collaboration and technology integration to support the development of digital-based prototypes.